Manajemen Kelas dalam Pembelajaran Al-Quran Metode Ummi di MTs Sunan Drajat Banjarwati Paciran Lamongan - Rizqa Yuhda Rohmah (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2022)
MTs Sunan Drajat Banjarwati Paciran Lamongan is one of the institutions located under the auspices of the Sunan Drajat Islamic Boarding School which has an Ummi method of learning Al-Quran learning program. To produce a good Quranic generation, it is necessary to have class management to create conducive classroom conditions, in order to overcome obstacles in student learning. So to describe how the implementation of the Ummi method in learning Al-Quran, this research was carried out. Research objectives 1) How is classroom management in the Ummi method of learning Al-Quran at MTs Sunan Drajat Banjarwarti Paciran Lamongan? 2) What are the problems and solutions for classroom management in the Ummi method of learning Al-Quran at MTs Sunan Drajat Banjarwati Paciran Lamongan? This research is a qualitative research that produces data and is analyzed using a descriptive method that is adapted to the Ummi method of learning Al-Quran at MTs Sunan Drajat Banjarwati Paciran Lamongan. The data collected using interview techniques, observation and documentation of the results of classroom management research in Al-Quran learning the ummi method as follows 1). Teacher planning to prepare PROTA (Annual Program) and PROMES (Semester Program), class grouping at the beginning of PPDB (New Student Admission) with the Pre-Test, regarding the implementation the teacher adjusts to the 7 stages that have been set by the teacher, evaluating there are several evaluations assessment during learning takes place, when UAS (School Final Examination) and UTS (Middle Semester Examination) increase in the last volume of Imtihan and Khotmil. 2). The problems and solutions are: lack of teachers in learning, student discipline with solutions must be brave to add 2 times more teachers during learning and with certified teachers, take Tahsin once a month.